Comparing the Minimum Income Standard in the UK and Japan: Methodology and Outcome. Issue 1 (30th July 2013) - Davis, Abigail; Hirsch, Donald; Iwanaga, Rie; Iwata, Masami; Shigekawa, Junko; Uzuki, Yuka; Yamada, Atsuhiro
<x content-type="archive" xml:space="preserve">Abstract</x> Minimum Income Standard (MIS) research involves an innovative methodology that combines consensual decisions made through discussion by members of the public, supported by input from experts. MIS addresses questions about income adequacy, and in particular, what is the income that people need in order to reach a minimum socially acceptable standard of living. The first MIS for Britain was published in the UK in 2008, and in 2010 researchers from Japan and the UK began to collaborate on developing a comparable Minimum Income Standard for Japan. This article discusses the differences and similarities between the UK and Japanese MIS. It looks at the challenges of applying the methodology in a very different setting and compares the results of the research in the UK and in Japan. Although there are notable differences in the lists of goods and services that comprise the budgets, there are also some striking similarities. This research suggests that the MIS methodology offers an approach that can be used in different countries to inform discussions on contemporary living standards and societal norms, and to enable international comparisons to be drawn.